Synergistic Study on n-Hexane Extract of Anredera cordifolia (Ten.)v Steenis (binahong) Leaves Combined with Antituberculosis Drugs against Drug-Sensitive and Drug-Resistant of Mycobacterium tuberculosis - Dian Ayu Eka Pitaloka, Elin Yulinah Sukandar (Journal of Applied Pharmaceutical Science, 2018)
Objectives: The aim of this study was to evaluate the antimycobacterial activity of Anredera cordifolia (Ten)v Steenis (binahong) leaves extract when it was combined with antituberculosis drugs against drug sensitive and drug resistant of Mycobacterium tuberculosis (MTB). Materials and Methods: H37Rv sensitive strain, streptomycin-rifampicin (SR) resistant strain, and isoniazid-ethambutol (HE) resistant strain were evaluated by susceptibility test by using a serial number of three different extracts of binahong with the range of concentration was 50 μg/mL-1000 μg/mL. Minimum Inhibition Concentration (MIC) was read as a minimum concentration of extracts that completely inhibited visible growth of the organisms. Synergistic study of extract with anti-tuberculosis (TB) drugs was determined by susceptibility test in Lowenstein Jensen (LJ) media by calculating the Fractional Inhibitory Concentration Index (FICI). Results: The results show that n-hexane extract of binahong leaves had better antimycobacterial activity compared to other extracts with the MIC was 500 μg/mL against H37Rv strain or SR strain of MTB and 250 μg/mL against HE strain. The combination of n-hexane extract and anti-TB drugs also displayed a synergistic interaction and no antagonism result from the combination was observed. Conclusion: These results indicated that n-hexane extract of binahong leaves may serve as a template for the development of novel antimycobacterial compounds. 1
Keywords: Anredera cordifolia, Mycobacterium tuberculosis, Drug combination, Susceptibility test.